Reproductive biology of the spiny eel Macrognathus pancalus Hamilton, 1822 from upper Assam, India - Abujam, S.K.; Biswas, S.P. (Indian Journal of Fisheries, 2020)
Reproductive biology of spiny eel Macrognathus pancalus Hamilton, 1822 was studied from the waterbodies of upper Assam, India. Sexual dimorphism was easily distinguished based on their body shape and colouration. Among the 467 fish samples examined, 312 males and 155 females were identified and the Male:Female (M:F) ratio ranged from 1:0.08 in November to 1:2.17 in June with overall sex ratio of 1:0.5. Five maturity stages were identified in a year and percentage distribution of each stage was calculated. The gonadosomatic index (GSI) ranged from 0.42 to 8.08 for females and from 0.33 to 1.25 for males. The length at 50% of the fishes attained maturity (Lm50) was 9-12 cm in males and at 12-15 cm in females, indicating males matures at moderately smaller size than their female counterparts. Ova diameter ranged from 0.3 to 1.3 mm; absolute fecundity ranged from 765.48 to 1691.96 and relative fecundity from 57.9 to 152.17. M. pancalus spawned once in a year with peak spawning between June and August. Â Â Keywords: Indian spiny eel, Macrognathus pancalus, Reproductive biology, Upper Assam